Bagaimana Memproyeksi Busy Book sebagai Media Belajar Bahasa Arab bagi Usia Dini? - Fina Aunul Kafi; Devi Miftahul Mahasin (INAIFAS Press, 2022)
Arabic language teachers at an early age need to have knowledge and skills in making learning media. This article explores the assistance in making busy books for ustadzah TPQ Al-Qodiri 2 Gumukmas Jember. This assistance article aimed to project the manufacture of busy book Arabic learning media for early childhood using flannel with ustadzah TPQ Al-Qodiri 2 Gumukmas Jember. This article used a Participatory Action Research approach by collecting data through in-depth interviews, sharing, focus group discussions, and questionnaires. The results of the assistance showed that the assisted partners gained knowledges and skills and had succeeded in making busy books and could be used as capital to be developed in other lessons. This assistance program can increase knowledge and creativity of assisted partners in processing flannel as a more effective medium for learning Arabic for early childhood.